The influence of brand image and customer experience on reuse intention with trust as a mediating variable: A study on sociolla users - Bargandini, Anak Agung Istri Syawana; Suparna, Gede (International research journal of management, IT and social sciences, 2025)
In Indonesia’s growing beauty e-commerce sector, customer reuse intention is vital for long-term survival, as retaining existing customers is a key factor. This study aims to explain the mediating role of trust in the relationship between brand image and customer experience on reuse intention at the e-commerce platform Sociolla. Using a quantitative approach with SEM-PLS, data were collected from 170 respondents via a Google Form questionnaire. The sample was selected using a purposive sampling technique. The findings indicate that brand image and customer experience both positively and significantly influence trust, which, in turn, boosts reuse intention. Additionally, trust was found to act as a partial mediator in the relationships between brand image, customer experience, and reuse intention. Theoretically, these findings contribute to the Theory of Planned Behavior by providing empirical evidence of how these variables are interconnected. The study also offers practical recommendations for Sociolla, such as utilizing brand ambassadors, enhancing customer service, ensuring transparency, and guaranteeing transaction security, to drive customer loyalty and retention.